Extraction and Purification of Fucoxanthin from Sargassum sp. as Anti-acne - Renhoran, Mawaddah; Noviendri, Dedi; Setyaningsih, Iriani; Uju, U. (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Fucoxanthin is a pigment of a carotenoid group in brown seaweed. Fucoxanthin has high biological activity, therefore, it is suitable for the antibacterial activity. Acne is a disease caused by bacterial activity. The purposes of this study were to obtain fucoxanthin active compounds of Sargassum sp. and to determine antibacterial activity of crude extract and fucoxanthin active fraction as anti-acne compounds at bacteria causing acne. Extraction of fucoxanthin used maceration method and its purification was carried out by silica gel column method. Antibacterial activity test used disk diffusion method.  The yield of crude extraction and yield of active fraction of Sargassum sp. were 0.54% and 0.13% respectively. Fucoxanthin active fraction was identified at 0.53 Rf value. The total content of fucoxanthin was 0.47 mg/g. The functional groups of fucoxanthin active fraction consisted of alcohols, alkanes, methyl, alkenes, esters and aromatic alkenes. Fucoxanthin active fraction had anti-acne activity at 125, 250, 500 and 1,000 ug/disk against of Propionibacterium acnes and at 500 and 1,000 ug/disk against of Staphylococcus aureus.